Teacher Difficulties on Online Learning in Economics Subject - Kurniawati, Susanti; Dahlan, Dadang; Parhah, Siti; Hilmiatussadiah, Kinanti Geminastiti (Universitas Pendidikan Indonesia, 2022)
This study aims to identify difficulties are experienced by teachers during online learning, compiling lesson plan, implementation, and evaluation process. This research was conducted in a survey on economics teachers throughout West Java, totaling 230 people. This research was conducted with a quantitative approach with an exploratory survey method. Data collection was carried out using an online questionnaire instrument. Furthermore, the data were analyzed by descriptive statistics. The results of this study indicate that there are difficulties for teachers in planning, implementing and evaluating learning. Difficulties in compilling lesson plan when determining learning methods will be used in online learning activities, difficulties in implementation include preparing students mentally/psychically to take part in learning, difficulties in choosing teaching media and facilitating active and creative learning. Evaluation difficulties consist of difficulties in evaluating student attitudes and using digital evaluation tools. Based on the results of this study, to increase the effectiveness of online learning through solving the difficulties faced by teachers, it is necessary to develop teacher competence in online learning strategies which include the development of methods, media, and evaluation tools that can increase student participation in online learning.